PENGARUH BELANJA MODALDAN DAU TERHADAP KEMANDIRIAN KEUANGAN DAERAH DAN PERTUMBUHAN EKONOMI KABUPATEN/KOTA DI PROVINSI BALI - Azari, Doni; Sutrisna, I Ketut (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2022)
ABSTRACT   The research was conducted for the 2013-2018 period with a sample size of 8 districts and 1 city. The type of data used in this research is secondary data. Secondary data used obtained the website of Bali Provincial Statistics Agency. Research objectives to be achieved: 1) to analyze the effect of capital expenditure and general allocation funds on regional financial independence in districts in Bali Province. 2) to analyze the effect of capital expenditure, general allocation funds, and regional financial independence on economic growth in districts in Bali Province. 3) to analyze the effect of capital expenditure and general allocation funds through regional financial independence on economic growth in districts in Bali Province. Analysis technique used is path analysis and the results of research on capital expenditures and general allocation funds have a significant positive effect on regional financial independence in districts in Bali Province. Capital expenditures and general allocations do not have a direct effect on economic growth, while regional financial independence has a significant positive effect on economic growth in districts in Bali Province. Capital expenditures and general allocation funds have an indirect effect on economic growth through regional financial independence in districts / cities in Bali Province. Keywords : Capital expenditures, general allocation funds, regional financial independence, economic growth .